Dao De Jing - Cai, Zhizhong, 1948- (Book collections on Project MUSE., 2020)
"How could the Dao De Jing, the beloved source of philosophical Daoism, ever be improved upon? Through illustrations by the beloved cartoonist C. C. Tsai. In this complete edition of the Dao De Jing, Tsai works his magic again, taking Laozi's cryptic philosophical language and turning it into episodes that both challenge and delight the reader. Tsai begins with Laozi's biography from the Shi Ji, then Laozi takes over, patiently explaining his ideas to earnest students. Soon, we become the students, as Laozi describes the spontaneity of natural processes, the paradoxical effects of ethical precepts, the limits of language, the values of simplicity, and most of all how to go with the flow. When is knowledge reduced to ignorance? When can something that is empty count as being full? When do good intentions go awry? Laozi is the master visionary, who is able to get to the mountaintop and see a perspective on life that escapes most of us. He is able to see the big picture that we see only when it's too late. Laozi take us into the subtle complexities of human existence, like a dramatic nineteenth century novel, but in bitesize chunks that tantalize and inspire. One of the most translated books in the world, Tsai makes the Dao De Jing fresh and relevant, and Laozi perches us on the mountaintop, ready to take in the wide vista and contemplate each fragment of meaning"--